Degradation and detoxification of distillery wastewater pollutants for environmental safety through bacteria: - (Journal of Advances and Scholarly Researches in Allied Education, 2020)
India, like many other developing nations, is concerned about the environmental degradationbrought on by fast industrialisation, urbanisation, and population growth. Increased research is needed tosuccessfully mitigate and solve the issues of environmental (soil, water, and air) pollution caused bynumerous harmful chemicals emitted from many natural and human activities and its detrimentalimpacts on living organisms. When it comes to eradicating organic and inorganic contaminants frompolluted sources, contemporary remediation techniques have shown to be better to their more traditionalcounterparts. Phenolic compounds, non-phenolic compounds, endocrine-disrupting chemicals, andheavy metals are only some of the most dangerous types of environmental contaminants. All throughoutthe world, governments are strongly supporting programmes that help reduce pollution. To ensure ourcivilization can continue to thrive while having a negligible effect on the environment, pollution must becontained or eliminated as soon as possible.